Aerobnye sposobnosti i kardiorespiratornaja vynoslivost' sportsmenov-skalolazov - Vavaev, A.V. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
Sports climbing was included 28 July 2016 in the sports program of the Olympic Games in Tokyo in 2020, which opened the first Olympic training cycle for climbers claiming to participate in the XXXII Olympic Games. The coaching team is required a thought-out plan for athletic training of the national team and the nearest reserve, an part of which is the testing complex of the scientific support, which need general and specific athletic and physiological targets (order of the Ministry of sports of Russia of October 30, 2015 No. 995). This task cannot be solved without a preliminary analysis of scientific literature on this issue, which will identify the key physical and physiological characteristics and their target (model) values that affect the athletic performance of climbers. This review is focused at the issue of aerobic power and cardiorespiratory fitnessof sport climbers.